Measuring mental health literacy : Adaptation and validation of the portuguese version of the mental health literacy Scale (MHLS) - Neto, David Dias (2021)
Understanding mental health literacy is essential for promoting empowerment and proactivity in patients, reducing stigma, and increasing population awareness. The constitutive dimensions of mental health literacy are still being researched, and instruments’ research can shed light on the involved processes. The Mental Health Literacy Scale (MHLS) is a self-report measure of mental health literacy. This study aimed to adapt the MHLS to Portuguese and evaluate mental health literacy in a broad sample. A broad sample of 337 individuals participated in the adaptation. Besides filling out the MHLS, the participants were invited to fill out a general lifestyle measure. The global results reveal a good internal consistency of the MHLS. A three-factor structure (i.e., attitudes towards mental illness, knowledge about mental illness, and the ability to recognize symptoms) explained 35% of the total variance. Despite not finding an association with the general lifestyle measure, the MHLS scored higher in women and individuals with higher schooling, as expected. The results reinforce the role of MHLS as a useful measure of mental health literacy. The identified structure is discussed in light of the current understanding and implications of this essential process.